2018
DOI: 10.1159/000485499
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab-Associated Chronic Inflammatory Central Nervous System Disease and Peroneal Nerve Injury in a Psoriatic Patient Refractory to Treatment: Case Report with 10-Year Follow-Up

Abstract: The tumor necrosis factor-α (TNF-α) antagonists infliximab, adalimumab, and etanercept have been approved for the treatment of chronic inflammatory diseases such as rheumatoid arthritis, ankylosing spondylitis, psoriasis, and psoriatic arthritis. Manifestations of demyelinating disease have been reported for patients receiving TNF-α antagonists. We describe a rare manifestation of a chronic inflammatory process affecting both the central and peripheral nervous system in a patient who received infliximab for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There were fourteen cases of worsening neurological disease despite cessation of anti-TNF therapy and several reports of new, clinically silent lesions detected on follow-up imaging. 202,[205][206][207][208][209][210][211][212][213][214][215][216] A case-control study in rheumatoid arthritis using a Canadian administrative claims and electronic medical records database showed a trend towards an increased rate of demyelination in 891 patients with no risk factors (for demyelination) with the authors suggesting that TNF antagonist therapy may increase risk of truly incident demyelinating events by ~30%, although failed to meet statistical significance (adjusted rate ratio 1.31 [95% CI 0.68-2.50]). 217 To date, trial and pharmacovigilance registry data have not shown any increased risk although this may relate to a low overall incidence, as well as exclusion of people at particular risk.…”
Section: Expert Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…There were fourteen cases of worsening neurological disease despite cessation of anti-TNF therapy and several reports of new, clinically silent lesions detected on follow-up imaging. 202,[205][206][207][208][209][210][211][212][213][214][215][216] A case-control study in rheumatoid arthritis using a Canadian administrative claims and electronic medical records database showed a trend towards an increased rate of demyelination in 891 patients with no risk factors (for demyelination) with the authors suggesting that TNF antagonist therapy may increase risk of truly incident demyelinating events by ~30%, although failed to meet statistical significance (adjusted rate ratio 1.31 [95% CI 0.68-2.50]). 217 To date, trial and pharmacovigilance registry data have not shown any increased risk although this may relate to a low overall incidence, as well as exclusion of people at particular risk.…”
Section: Expert Consensusmentioning
confidence: 99%
“…Of 84 cases of central demyelination reported in patients with psoriasis, the majority occurred within the first year of therapy; 33% (25/76) achieved complete recovery after cessation of anti‐TNF +/− adjunctive therapy, 72% (55/76) did not achieve complete clinical recovery after cessation of TNF antagonist therapy. There were fourteen cases of worsening neurological disease despite cessation of anti‐TNF therapy and several reports of new, clinically silent lesions detected on follow‐up imaging 202,205–216 …”
Section: Guidance For Specific Clinical and Comorbid Situationsmentioning
confidence: 99%
“…Other serious side effects include an increased risk of lymphoma, reactivation of TB, and an increased risk of fungal infections [82]. Infliximab may also contribute to the exacerbation of demyelinating diseases and is not preferred in patients with multiple sclerosis [112,113]. Please see full prescribing information for complete list.…”
Section: Infliximabmentioning
confidence: 99%
“…Other serious side effects include an increased risk of lymphoma, reactivation of TB, and an increased risk of fungal infections [82]. Infliximab may also contribute to the exacerbation of demyelinating diseases and is not preferred in patients with multiple sclerosis [112,113]. Please see full prescribing information for complete list.…”
Section: Infliximabmentioning
confidence: 99%